Smart Integration - Korczak, Jerzy (University of Wroclaw. Faculty of Law, Administration & Economics, 2019)
The article is devoted to smart integration taking place on the Polish–German borderland and, more precisely, the border between the Lower Silesian Voivodeship and the Saxony Länder, which, according to the author, is the result of an evolution of forms of transfrontier cooperation of territorial self-government units. It will analyse the conditions for the emergence of forms of cooperation in the transfrontier area and their evolution in European experiences to date and, after 1990, also with the involvement of Polish territorial self-governments.
Keywords: euroregion; inteligentna administracja; umowa; transgraniczna przyroda; współpraca jednostek samorządu terytorialnego